ANALISIS USAHA PEMBIBITAN IKAN NILA POLA KEMITRAAN ANTARA KELOMPOK TANI MINA SOKA MAKMUR PT. AQUA FARM NUSANTARA DI KECAMATAN KALASAN KABUPATEN SLEMAN - Agus Santosa; Wulandari Der; Ook Anang Wijaya (Jurnal Dinamika Sosial Ekonomi, 2010)
This study aims to determine the electiveness of the partnership between the Fish Farmer Group Mina Sofa and PI Aquafarm Nusanfaro in Punvomartani villages, Kalasan District, Sleman Regency. Knowing the benefits ofagribusiness Breeding pattern ofcooperation between PT Aquafarm Nusantara with farmers who are members ofjish Farmers Group Alina Makmur Purwomartani village, Kalason Dis-trict, Sleman Regency 7he method used is descriptive method whereas exercise is a case method and sampling method using a census, the method of complete enumeration with the meaning ofall members of the population was counted as a respondent. The results showed that Tilapian Fish Breeding Business Partnership between Fish Farming Group Mina and PT Aquafarm Nusantara Punvormatani tillage Kalosan District Sleman Regency fective with the level ofejectiveness of26. 07%. Breeding business partnership between the Fish Furmer Group Mina Makmur and PT Aquafarm Nusantara in Pzmvomartani tillages, Kalasan District Slemon Regency Profitable for Fish Farming Group amounted to Rp 2. 199. 033, 33.Keywords effctiveness, benefits.